2022
DOI: 10.1021/acsami.2c06186
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating the Low-Temperature Catalytic Oxidation of Acetone over Al-Substituted Mn–Al Oxides by Rate-Limiting Step Modulation

Abstract: In order to enhance the catalytic activity and improve the stability of Mn–Al oxides in acetone oxidation, it is interesting to have found that modulating and accelerating the rate-limiting step by Al substitution rather than just mixing of Mn and Al is crucial for hydrocarbon efficient catalytic destruction. Here, a series of Mn–Al oxides with different Al substitution ratios were prepared by a scalable and facile hydrothermal-redox strategy. The reaction rate, selectivity, and stability of the representative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…peaks were assigned to the characteristic peaks of tetrahedral sites (Co 2+ −O). 35 22,38,39 The binding energy of O 1s on the MnO 2 /CoAlO-F catalyst shifted to lower energy in comparison to MnO 2 /CoAlO-P, while a similar phenomenon was observed on CoAlO-F and CoAlO-P (Figure 3b). This suggested that flowerlike MnO 2 / CoAlO-F (CoAlO-F) might possess more oxygen vacancies than platelike MnO 2 /CoAlO-P (CoAlO-P).…”
Section: Surface Metal States and Oxygen Speciesmentioning
confidence: 54%
See 2 more Smart Citations
“…peaks were assigned to the characteristic peaks of tetrahedral sites (Co 2+ −O). 35 22,38,39 The binding energy of O 1s on the MnO 2 /CoAlO-F catalyst shifted to lower energy in comparison to MnO 2 /CoAlO-P, while a similar phenomenon was observed on CoAlO-F and CoAlO-P (Figure 3b). This suggested that flowerlike MnO 2 / CoAlO-F (CoAlO-F) might possess more oxygen vacancies than platelike MnO 2 /CoAlO-P (CoAlO-P).…”
Section: Surface Metal States and Oxygen Speciesmentioning
confidence: 54%
“…At 180 °C, more formate than acetate species were observed on MnO 2 /CoAlO-F. This suggested that more acetate species were converted into formate species, and this conversion rate was higher than the conversion rate of formate into CO 2 and H 2 O, which was ever reported by He et al (the energy barrier for the conversion of acetate to formate was lower than that of formate to CO 2 and H 2 O) . This was the reason that more formate species were formed on MnO 2 /CoAlO-F in comparison to acetate species.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…47 The peak at 1370 cm −1 is ascribed to the stretching vibration of � CH 3 . 20 The band at 1231 cm −1 is ascribed to the stretching vibration of the carbon framework from acetone on the catalyst surface. 47 The peaks at 1415 and 1346 cm −1 are assigned to the symmetrical stretching vibration of carboxylate at acetate and formate species, respectively.…”
Section: 4mentioning
confidence: 99%
“…The Al is not a part of the main active phase, and the key role of Al is to disperse the active phase and adsorb acetone. 17,20 Therefore, the single metal oxide phase with highly homogeneous dispersion of Al species in the Al-based materials fully exhibits their own activity and synergistic effect, which promotes efficient catalytic oxidation of acetone. Until now, the effects of composition ratio and crystal phase of the whole material on catalytic activity have been widely investigated for Al-based catalysts.…”
Section: Introductionmentioning
confidence: 99%